A midsummer night's dream - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
A comedy written by William Shakespeare in 1595/96. The play consists of multiple subplots that revolve around the marriage of Theseus and Hippolyta. One subplot revolves around a conflict between four Athenian lovers, one about a group of six amateur actors who have to act out their interpretation of the play 'Pyramus and Thisbe' at the wedding of Theseus and Hippolyta. These subplots take place in a forest, inhabited by fairies who control the characters of the play. The play is one of Shakespeare's most popular works for the stage and is widely performed across the world.
Keywords: Theseus, King of Athens -- Drama; Athens (Greece) -- Drama